First report of a perforated abomasal ulcer in a beef heifer calf in Argentina - Perez Gaudio, Denisa; Perez, Flavio; Bretschneider, Gustavo (The Chamber of Veterinary Surgeons, Istanbul, 2020)
Abomasal ulcers are local processes of autodigestion of the mucosa caused by the disturbance of the balance between protective and aggressive mechanisms at the abomasal mucosa. Several causes have been suggested and a multifactorial origin has been proposed. Signs are mostly non-specific and vary among the different ulcer types. This report describes for the first time in Argentina the clinical case of a perforated abomasal ulcer that induced sudden death in a heifer calf at foot dairy. At necropsy, digestive content in the abdominal cavity and two ulcers in the abomasum mucosa were evident. One ulcer had a well-defined 3 cm diameter perforation. Its leading cause has not been determined. To minimize the risk of developing perforated abomasal ulcers, stressful management practices should be avoided.